Topoisomerase-II mediated DNA damage: role of BRCA1 and other chromatin structure regulators - Alves, Inês Teles, 1985- (2013)
Tese de mestrado. Biologia (Biologia Molecular Humana). Universidade de Lisboa, Faculdade de Ciências, 2009